Obturator nerve endometriosis: A systematic review of the literature - Kale, A.; Aboalhasan, Y.; Gundogdu, E. C.; Usta, T.; Oral, E. (UNIVERSA PRESS, 2022)
Background: Symptomatic obturator nerve endometriosis is a rare condition. In this paper, we aim to review and discuss the characteristics of obturator nerve endometriosis in light of current literature.Methods: An electronic search was conducted using the PubMed/Medline database.Results: Symptomatic obturator nerve endometriosis is rare

only 8 cases have been reported in the literature. Symptoms including difficulty walking, weak thigh adduction and pain in the inner thigh, which are all related to obturator nerve function, could be seen in the case of the entrapment of the nerve by endometrial nodules. A history of recurrent symptoms during menstrual cycles and physical examination, combined with appropriate radiologic imaging, led to a suspicion of obturator nerve involvement.Conclusion: Early diagnosis and surgical treatment of obturator nerve endometriosis is essential to minimise the nerve damage caused by recurrent cycles of bleeding and fibrosis, which are characteristics of endometriosis. The laparoscopic minimally invasive technique is feasible for the surgery of obturator nerve endometriosis. It offers the advantage of precise discrimination of vital structures and excellent access to deep anatomic sites. What is new? Obturator nerve endometriosis may be a severe cause of chronic pelvic pain in women of reproductive age. Treatment may be achieved surgically and in experienced hands, laparoscopic surgery would be the preferred choice.
Keywords: endometriosis; deep infiltrating endometriosis; obturator nerve; laparoscopy